A social enterprise for an online animal welfare knowledge community - Del Rosario, Kathleen O.; Cruz, Edison (Quezon City University of the Philippines Diliman, 2017)
The Philippine government and several animal welfare groups had taken initiatives to educate and raise awareness on the prevention of animal cruelty and responsible pet ownership in our country. Nongovernment organizations (NGOs) are the also active in implementing animal welfare laws and in addressing these issues.
This project aims to establish a social enterprise for an online animal welfare knowledge community that will provide a platform for creating, storing, and retrieving information, making these contents accessible via one platform that can address the problems of information clutter. This online platform can also be a venue where animal welfare groups and communities can interact, making this social action appealing to existing and potential animal welfare advocates. The online platform aims to earn through advertising that will be used solely for sustaining the site's operation and for donating to partner animal shelters.
The online platform's prototype is named Manila Animals Online (MAO) and is deployed to serve as one of the references for an online survey. The survey intends to know the awareness level of the public on animal welfare laws, the need for an online knowledge community, and if they are willing to participate in the said community. Half of the respondents of the survey agreed that online is the best platform for this endeavor, and ninety-two percent (92%) thinks that a knowledge community should be established for this cause. Other points reiterated by the respondents are the importance on how the audience can be reached for social awareness, information dissemination and exchange, as well as proper education and guidance.
Participant observation is also used as a data gathering method to have a hands-on experience on being a volunteer, to know the potential members of the online community, and to figure out how the website can be improved in terms of content.
The opportunities considered for this project are to either expand the MAO team for the expansion and maintenance of the online platform, or to transfer the ownership to an established animal welfare group. The business plan created for this project sets MAO's mission, and serves as a primer for MAO's future team. Seeing that there are still more work to be done in order for MAO to gain its ground in site rankings and to develop the site's contents, it is to be noted that perseverance and dedication are key in sustaining MAO and its advocacy.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Animal welfare -- Philippines; Animal welfare -- Law and legislation -- Philippines; Knowledge community